The global strategy on public health, innovation and intellectual property: establishment of a priority order for research and development needs in Brazil - Lima, Jordão; Dallari, Sueli (Saúde e Sociedade, 2020)
The adoption of the Global Strategy and Plan of Action on Public Health, Innovation and Intellectual Property (GSPOA) within the framework of the World Health Organization (WHO) is based on the need to improve the access conditions of developing countries to medicine and other products that meet their specific public health needs. This study verifies the implementation of the first GSPOA Element in Brazil, which refers to the establishment of an order of priority for research and development needs. This qualitative case study was based on a critical perspective and established theoretical frameworks, seeking to place GSPOA in a transnational health context in an era of globalization, and to discuss the challenges to more fully implement a right to health that transcends the use of medicines and individual requirements. We concluded that, from 2008 to 2015, Brazil was successful in developing methodologies and mechanisms to identify and disseminate the gaps in the research of diseases of greatest incidence in the country and their consequences on public health, guiding the development of feasible and affordable therapeutically products.